PETE`-PETE` DAN SEJARAHNYA (ATAU TENTANG POLITIK INGATAN DI KOTA MAKASSAR) - Asri, Syamsul (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2015)
This article analyzes the existence of ‘pete-pete’, one mode of public transports in Makassar as a social reality, delving into the crust of its meaning, its socio-history and the changes of its meaning within the society. Along with the global development, ‘pete-pete’ has gone through multi meanings, not only as one mode of public transports, but also as a medium, an actor, and even a stage for activists to fundamentally establish public spaces for social interaction. Moreover, ‘pete-pete’ is also an entity to willingly attract political power on a regular basis, through social discourses or implementation of urban planning. Keywords: ‘Pete-pete’, public space, social interaction, political power